Biodegradable trays made from Poraqueiba sericea Tulasne seed starch and Zea mays cob flour (Scientia Agropecuaria, 2024)
The environmental impact of polystyrene and other petrochemical packaging has increased interest in researching biodegradable materials as alternatives. The main objective of this research was to develop biodegradable trays from five formulations of Poraqueiba sericea Tulasne (known as umari) seed starch and corncob meal. The trays were produced using the thermoforming process applying temperatures of 135 °C and 145 °C for each side of the tray for a time of 6.5 min. Physical analysis of the trays showed that the increase in the percentage of corn cob flour caused changes in color (L*: 68.69 - 64.94), thickness (2.20 - 3.17 mm), density (0.251 - 0.414 g/cm3), moisture (3.85% - 5.68%), water absorption (21.86% - 39.05%), volatile solids (95.33% - 98.31%). Regarding mechanical properties, it was also evidenced the increase in hardness (67.70 - 90.97 N), fracturability (1.43 and 3.19 mm), tension (2.84 to 3.43 MPa) and elongation (1.54% to 2.04%). The formulation of 87.5% umari seed starch and 12.5% corncob flour presented more favorable physical and mechanical properties. Further analysis of this formulation was performed by Fourier transform infrared spectroscopy (FTIR), which identified bands characteristic of starch (1055 and 1027 cm-1); X-ray diffraction (XRD), which revealed characteristic peaks (2θ = 16.83° and 2θ = 22.69°) associated with cellulose crystallinity in the biodegradable tray; and scanning electron microscopy (SEM), which revealed cellulosic voids with irregular distribution due to the addition of fibers. Future research should examine the potential applications of these biodegradable trays for the packaging of raw materials in the food industry.